On Pancratium maritimum (sea daffodil, sea lily, sand lily) - John Pouris; Sophia Rhizopoulou (Horticulture International Journal, 2018)
The perennial geophyte sea daffodil, sea lily or sand lily (Pancratium maritimum L.) is a flowering species during the dry summer, widely distributed along Mediterranean seashores and grown in a wild stage. Populations of sea daffodil are exposed to sea breeze, salt spray, water shortage, strong solar radiation, elevated temperatures, substrate instability and moving sand. Also, it is expected that excessive tourism and human-induced activities will constrain the development of populations of P. maritimum, which have resulted from a long-term evolutionary process. P. maritimum exhibits large white flowers of a great aesthetic value during dry and hot summer weather conditions, when simultaneously flowering plant taxa are scarce. The buds remain protected below the soil surface on the underground perennial organ and the growth period alternates with a period of dormancy. The above-ground organs and tissues are exposed to harsh, ambient conditions and the large inflorescences of remarkable beauty and fragrance carry particular ornamental worth and thus economic value.